Neoadjuvant chemotherapy in patients with locally advanced gallbladder cancer. (May 2015) - Sirohi, Bhawna; Mitra, Abhishek; Jagannath, Palepu; Singh, Ashish; Ramadvar, Mukta; Kulkarni, Suyash; Goel, Mahesh; Shrikhande, Shailesh V
ABSTRACT : Aim: Surgery is the only curative option for patients with gallbladder cancer (GBC). This study looks at the outcome of patients treated with neoadjuvant chemotherapy (NACT).Patients & methods: This is retrospective analysis of the prospectively maintained database of patients with locally advanced GBC treated between February 2009 and September 2013 with NACT. Patients received gemcitabine-platinum based regimen.Results: A total of 37 patients (median age: 54 years, 64.9% females) received NACT. Overall response rate was 67.5%. In total, 17 patients (46%) underwent R0 resection. Median overall survival/progression-free survival of the whole group was 13.4/8.1 months, respectively. Patients who underwent surgery had a significantly better overall survival (median not reached vs 9.5 months) and progression-free survival (25.8 vs 5.6 months), respectively.Conclusion: NACT increases resectability and survival in patients with locally advanced GBC.